Effect of step length optimization on the aerobic demand of running - Morgan, D.; Martin, P.; Craib, M.; Caruso, C.; Clifton, R.; Hopewell, R. (Journal of Applied Physiology, 1994)
To assess whether distance runners displaying uneconomical freely chosen step lengths (FCSL) could be trained to shift FCSL toward a more optimal setting, six males and three females who exhibited uneconomical FCSL [mean optimal step length (OSL) = -9.81% of leg length from FCSL; mean change in oxygen uptake (VO2) (FCSL - OSL) = 1.46 ml.kg-1.min-1] comprised an experimental group that completed 15 treadmill sessions (30 min/day, 5 days/wk, 3 wk) of OSL training at individually determined running velocities (2.87-3.74 m/s). Training sessions featured alternating 5-min periods of combined audio and visual feedback matching OSL and no feedback. A control group of three subjects with uneconomical FCSL (2 males, 1 female) performed 3 wk of treadmill running without feedback. The extent of step length optimization was evaluated by comparing pre- and posttraining differences between FCSL and OSL and between pre- and posttraining VO2. Compared with the control group, the experimental group demonstrated a significantly (P < or = 0.05) greater relative shift in FCSL toward OSL and a marked reduction in FCSL VO2. Taken together, these results suggest that short-term audiovisual feedback training can be effective in optimizing step length and producing a decrease in aerobic demand among distance runners exhibiting uneconomical FCSL.